A study on demographic information of the respondent in cross-border marriage: an empirical evidence from the state of Perlis - Md Said, Muhamad Helmi; Md Hashim, Noraini; Abdul Hak, Nora; Che Soh @ Yusoff, Roslina (Universitas Muhammadiyah Yogyakarta, 2017)
Marriage is a sacred bond, a tie between a man and a woman. Such relationship is blessed by Allah as it is mentioned in the Quran and the tradition (Sunnah) of the Prophet (pbuh). The laws created by man are meant to streamline the conduct of marriage, apart from the already provided hukm laid down in Islam. However, there are people who tend to violate these laws due to their own ignorance and this violation affects the future of such marriage and as well other people who are attached to it. Cross-border marriage is a marriage without permission from the registrar of marriage in each States and its solemnisation can be contracted in Malaysia or outside Malaysia. The purpose of this study is to examine and analyse the demographic profiles among the respondents towards the factors of cross-border marriage among Mus- lims in Malaysia. The expected sample consists of 100 respondents from one selected state in north Malaysia, bordering Thailand namely Perlis. The questionnaire survey is the main data collection method employed in this study and further supported by semi- structured interview. Based on the findings, the respondents are expected to adhere and abide the regulation and policy in controlling cross-border marriage from worsening in the future.